Connecting the Fragmented Forests by Opportunity of Vertical Dual Land Use-II (Plantation of Dwarf Species, Preferably Medicinal Plants in RoW of Transmission Lines as Compliance of the Existing Mandatory Condition under FC Act, 1980) - Misra, Vinay Kant (Indian Forester, 2024)
Plantation of dwarf species (preferably medicinal plants) in right of way (RoW) of transmission lines is a unique mandatory condition in the projects of forest land diversion under Forest (Conservation) Act, 1980. It provides a unique opportunity of vertical dual land use by differentiating the vertical space above land for different uses. In part-I of the present study, various aspects of the existing practices including safety, species selection, spacing of seedlings, phytoclimatic zones and vegetation types was given based on review of 1080 projects of forest land diversion for transmission lines. A differential height model of plantation and method of calculation of available vertical space and also horizontal space (K-value) for relatively taller (T-value) dwarf plants was given. A list of 200 perennial dwarf species of different phytoclimatic zones of India was given along with their distribution and available propagation techniques. In the present part-II of this study, 50 more perennial dwarf plant species are being added. The information on palatability/edibility of various parts of 83 dwarf species (including few from the list of part-I of this study and 50 in present article) for wildlife is given. Detailed plan of plantation of dwarf species is given including lay-out, cost analysis and fencing. The bamboo fencing is proposed for forest areas in place of present common practice of barbed-wire fencing along with comparison of costs of different types of prevailing fencing practices. The rate of levy of dwarf species plantation is proposed along with the method to calculate levy demand in future years.